Validation of Revised Chinese Version of PD-CRS in Parkinson's Disease Patients. (19th February 2020) - Tan, Yuyan; Liu, Weiguo; Du, Juanjuan; Hou, Miaomiao; Yu, Cuiyu; Liu, Yang; Cui, Shishuang; Yan, Lei; Lu, Yizhou; Lv, Hong; Han, Lijun; Wang, Xi; et al.
Abstract : There is a high prevalence of mild cognitive impairment (MCI) and dementia in Parkinson's disease (PD) patients, but a Chinese version of cognitive rating scale that is specific and sensitive to PD patients is still lacking. The aims of this study are to test the reliability and validity of a Chinese version of Parkinson's disease-cognitive rating scale (PD-CRS), establish cutoff scores for diagnosis of Parkinson's disease dementia (PDD) and PD with mild cognitive impairment (PD-MCI), explore cognitive profiles of PD-MCI and PDD, and find cognitive deficits suggesting a transition from PD-MCI to PDD. PD-CRS was revised based on the culture background of Chinese people. Ninety-two PD patients were recruited in three PD centers and were classified into PD with normal cognitive function (PD-NC), PD-MCI, and PDD subgroups according to the cognitive rating scale (CDR). Those PD patients underwent PD-CRS blind assessment by a separate neurologist. The PD-CRS showed a high internal consistency (Cronbach's Alpha = 0.840). Intraclass Correlation coefficient (ICC) of test-retest reliability reached 0.906 (95% CI 0.860–0.935, p < 0.001 ). ICC of inter-rater reliability was 0.899 (95% CI 0.848–0.933, p < 0.001 ). PD-CRS had fair concurrent validity with MDRS (ICC = 0.731, 95% CI 0.602–0.816). All the frontal-subcortical items showed significant decrease in PD-MCI compared with the PD-NC group (p ≤ 0.001 ), but the instrument cortical items did not (confrontation naming p = 0.717, copying a clock p = 0.620 ). All the frontal-subcortical and instrumental-cortical functions showed significant decline in PDD compared with the PD-NC group (p ≤ 0.001 ). The cutoff value for diagnosis of PD-MCI is 80.5 with the sensitivity of 75.7% and the specificity of 75.0%, and for diagnosis of PDD is 73.5 with the sensitivity of 89.2% and the specificity of 98.9%. Revised Chinese version of PD-CRS is a reliable, acceptable, valid, and useful neuropsychological battery for assessing cognition in PD patients.